MITIGASI PERFORMA KENDARAAN FOAM TENDER TERHADAP PELAYANAN BANDAR UDARA INTERNASIONAL MINANGKABAU PADANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the suitability of the performance of the Foam Tender vehicle of the PKP-PK unit at Minangkabau Padang International Airport to the response time standards stipulated in the Decree of the Director General of Civil Aviation Number PR 30 of 2022. Based on the results of observations, interviews, and documentation, it was found that one of the main vehicles, namely Foam Tender 03, was unable to achieve the required response time, due to declining vehicle performance due to its age of 20 years and less than optimal technical conditions. The study used a descriptive qualitative method with data collection techniques through direct observation, interviews with PKP-PK personnel, and field documentation. The analysis was carried out using a gap analysis approach to compare actual conditions with the desired standards. The results of the study indicate that mitigation efforts carried out include the use of other vehicles that still meet standards, the implementation of routine maintenance and repairs, and the proposal to replace vehicles with new units such as the Ziegler Z6. These findings are expected to be used as evaluation material and recommendations for airport managers in improving the quality of safety services and emergency preparedness at the airport.